PENGARUH PEMBERIAN TEH ROSELLA (HIBISCUS SABDARIFFA) TERHADAP KADAR SUPEROXIDE DISMUTASE (ANTIOKSIDAN TUBUH UTAMA) PADA TIKUS JANTAN REMAJA YANG DIBERI ALKOHOL - Budi ekanto; Syamsudin -; tulus Puji Hastuti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2012)
Increase systolic blood pressure that related with impairedvasodilatation of the arterioles is affected by the decrease of NO level andincrease peroxynitrite. Nitric oxide level may be reduced by increase ofSuperoxide production that due to alcohol consumption. Superoxidedismutase activity will be decreased by its role in preventing reaction ofSuperoxide with NO to form peroxynitrite. Superoxide is reduced by SODto form hydrogen peroxide and oxygen. Oxidative stress due to alcoholconsumption lead to lower NO level and SOD activity in the blood. Theaims of this study are to examine the influence of rosela tea to the SODlevels in blood serum in rats given doses of alcohol 30 % 3 g / kg bodyweight / day.Thirty male of Wistar rats with weight 150 grams were divided intofive groups, each group consists of 6 animals. Group A was controlgroup. Group B was given by alcohol. Group C, D, E were given byalcohol and rosela. Doses 0.75 gram of dried rosela that diluted by 200cc of water gave to group C, while group D was given by rosela dose 1.5grams and 3 grams to E group. Providing alcohol and rosela conductedover 28 days by orally (orogastric tube). Rosela was given at 08.00 amand alcohol at 10:00 am. SOD levels in blood are measured aftertreatment. Results showed that Superoxide dismutase levels of groupthat were given by alcohol and 0.75 g, 1.5 g, 3 g rosela higher than thosein group that received only alcohol and control. Conclussion, rats thatwere given by rosela tea and alcohol have higher SOD level compared tocontrol group.Keywords : alcohol, rosela, Nitric oxide, SOD